Fostering Musical Creativity with Digital Audio Workstations: An Action Research - Nurfalah, Asep Rizwan; Narawati, Tati; Budiman, Agus (Gondang: Jurnal Seni dan Budaya, 2025)
The development of digital technology, especially artificial intelligence (AI), has had a significant impact on education, including music learning. Digital Audio Workstations (DAWs) equipped with AI features offer opportunities to create more interactive and innovative learning. This study aims to explore the role of AI features in DAW as a creative learning medium in the extracurricular music of SMAN 8 Bandung, as well as provide new information on its impact on enhancing students' creativity. This study used a qualitative approach based on action research involving students participating in extracurricular music as research subjects. Data were collected through participatory observation, semi-structured interviews, and document analysis in the form of students' musical works. The data were analyzed using triangulation techniques to ensure the validity and reliability of the findings. The results showed that the use of AI features, such as automatic composition, sound processing, and harmony analysis, made it easier for students to understand musical concepts and encouraged them to create innovative works. In addition, the AI features helped students overcome technical obstacles, allowing them to focus more on the creative process. This results in increased student motivation and engagement in music learning. This study concludes that the integration of AI in DAW provides a great opportunity for educators to develop creative and relevant technology-based learning methods. As a recommendation, the implementation of this technology needs to be expanded and integrated with the curriculum to support learning in the digital era.